Investigation on the esterification of fatty acids catalyzed by the H3PW12O40 heteropolyacid - Cardoso, Abiney L. (2008)
In this work, the H3PW12O40 heteropolyacid (HPW) was employed as a homogeneous catalyst to promote the efficient esterification (ethanolysis) of a number of saturated and unsaturated fatty acids (myristic, palmitic, stearic, oleic, and linoleic) under mild reaction conditions. HPW showed a similar activity to those observed for p-toluene sulfonic acid (PTSA) and sulfuric acid (H2SO4), the other acidic catalysts we compared them with in this study. In the HPW-catalyzed esterification of stearic acid, the addition of water caused a remarkable decrease in the ethyl stearate yields. On the other hand, the increase in the HPW concentration (up to a maximum value) promoted a proportional improvement in the oleic acid to ethyl oleate conversion. Kinetic measurements using oleic acid as a prototype substrate revealed that the esterification reactions catalyzed by HPW, H2SO4, and PTSA are of first-order in relation to the fatty acid concentration. Finally, the catalytic activity of HPW remained unaltered even after several recovery/reutilization cycles whereas the tungsten content in the final product (biodiesel produced by the HPW-catalyzed esterification of oleic acid) was found to be at an acceptably low level (0.0095 mg of W per g of biodiesel).